Model Pembelajaran Inkuiri dalam Mendorong Berpikir Kreatif Siswa Kelas V MI pada Pembelajaran IPA - Salma, Alma Sakinatu; Carlian, Yayan; Ginanjar, Ani Yanti (Universitas Garut, 2025)
This study aims to investigate the extent to which the implementation of the inquiry-based learning model impacts students' creative thinking skills in science subjects. A quantitative approach was adopted, utilizing a quasi-experimental design with a non-equivalent control group structure. A total of 52 fifth-grade students from a Madrasah Ibtidaiyah (MI) in Bandung City were purposively selected as participants. They were assigned into two groups, comprising 26 students each in the experimental and control classes. An instrument consisting of 8 essay items was administered during both the pretest and posttest phases to assess students’ creative thinking skills. The findings indicated a statistically significant enhancement in the experimental group following the application of the inquiry model, with a posttest average score of 77.8 and an N-Gain of 0.67, classified within the moderate category. These findings affirm the effectiveness of the inquiry approach in fostering divergent thinking and enhancing students’ adaptability in problem-solving. This study offers a practical contribution in providing evidence-based recommendations for elementary science instruction, emphasizing the integration of inquiry-based strategies to cultivate students’ higher-order creative thinking competencies. Keywords: inquiry learning model, creative thinking skills, IPA